Reduced Production of Pro-Inflammatory and Pro-Catabolic Factors by Human Serum Metabolites Derived from a Patented Saffron Extract Intake - Line Pourtau; Fabien Wauquier; Line Boutin-Wittrant; David Gaudout; Benjamin Moras; Adeline Vignault; Carole Vaysse; Tristan Richard; Arnaud Courtois; Stéphanie Krisa; Véronique Roux; Nicolas Macian; et al. (Pharmaceutics, 2024)
Safe and anti-inflammatory plant-based natural products present an increasing focus in the treatment of chronic inflammatory diseases such as osteoarthritis or inflammatory bowel diseases. Among them, saffron, a spice derived from the stigma of Crocus sativus, could have anti-inflammatory properties and would be therefore a promising therapeutic agent for the treatment of such conditions. However, the anti-inflammatory molecular mechanisms of saffron in humans are still understudied and unclear. In this study, combining human serum metabolites and cell cultures, we evaluated the effect of circulating metabolites from the consumption of a patented saffron extract (Safr’InsideTM) on the chondrocytes and colon epithelial cell responses to inflammatory stress. Parametric or non-parametric Analysis of Variance with post hoc tests was performed. We demonstrated that human serum containing metabolites from saffron intake attenuated IL-1β-stimulated production of PGE2 and MMP-13 in chondrocyte cells and limited the increase in ICAM-1, MCP-1, iNOS, and MMP-3 in human epithelial cells following combined IL-1β and TNF-α inflammatory stimulation. Altogether, these data provide new findings into the mechanisms underlying the beneficial effects of saffron on chondrocytes and enterocyte cells at the cellular level and in the context of chronic inflammatory disorders.